Geological mapping of Litla Sandfell a glaciovolcanic eruption - Birta Dís Jónsdóttir Blöndal 1997- (2022)
Litla Sandfell is a small mountain located in the south of Iceland close to Þrengslavegur. It is 80m high and measures around 600-700m in length. The volume of the mountain is 0.01189km3. It is documented that Litla Sandfell is mainly Tuff from a subglacial fissure eruption that occurred in the Weichselian, the last glacial period. It is classified as a tuya since it protruded thru the glacier during the eruption, causing the glacier to melt and lava flowed into the glacial lagoon. Once the eruption was over the glacier covered the mountain transporting sedimentary deposits that overlaid Litla Sandfell as a glacial envelope. Holocene lava named Leitarhraun surrounds the mountain covering the roots. Fissures in the area are oriented SV-NE and are still active and can be seen today through Leitarhraun. The material and rock types of the mountain were examined with XRD, XRF, normative calculations and thin sections. Seven different types of material were found and divided as follows: A: Basalt that cuts through the mountain and can be observed on the surface in some places. The basalt appears as three different types divided to Pillow Lava, Pillow Breccia and Lava flow. B: Loose tuff mixed with basalt stones that overlies the whole mountain and seems to be the majority of material found in Litla Sandfell. C: tuff that has undergone palagonitization and therefore display yellowish colours. D: “Stone carpet” that consists of basalt rocks and tuff. It overlies the top of the whole mountain. E: A collapse from the walls above and is a mixture of all materials. F: Glacial envelope with rounded pebbles to cobbles indicating transportation and erosion of the material located in the matrix which consist of sedimentary deposits and tuff. The structure is deformed and wavy after the pressure from the glacier. G: Material from previous eruption that lies beneath Litla Sandfell. The material consists of tuff mixed with basalt rock. Litla Sandfell er lítið fjall á Suðurlandi skammt frá Þrengslavegi. Það er 80 metrar á hæð og ...